2008
DOI: 10.1111/j.1464-410x.2008.08025.x
|View full text |Cite
|
Sign up to set email alerts
|

Advanced‐stage renal cell carcinoma treated by radical nephrectomy and adjacent organ or structure resection

Abstract: OBJECTIVE To examine the effect of radical nephrectomy (RN) with adjacent organ and structure resection on survival, as invasion of adjacent organs in patients with renal cell carcinoma (RCC) is rare. PATIENTS AND METHODS After institutional review board approval, we reviewed our database and statistically analysed of patients with pathological stage T3 or T4 RCC who had RN and resection of a contiguous organ or structure. RESULTS We identified 38 patients of 2464 (1.5%) who had RN with adjacent organ or struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 19 publications
1
17
0
1
Order By: Relevance
“…The patient was alive and well at 5 years 3. Karellas et al reported improved survival with extended resection 5. Applying bipolar radiofrequency energy to an electrode array can enable transmural excision of renal parenchyma in a bloodless way (figure 2B) without incurring system injury6 and without renal pedicle clamping 7.…”
Section: Discussionmentioning
confidence: 94%
“…The patient was alive and well at 5 years 3. Karellas et al reported improved survival with extended resection 5. Applying bipolar radiofrequency energy to an electrode array can enable transmural excision of renal parenchyma in a bloodless way (figure 2B) without incurring system injury6 and without renal pedicle clamping 7.…”
Section: Discussionmentioning
confidence: 94%
“…As reflected in the 2010 AJCC TNM staging, patients with tumor extension beyond Gerota’s fascia are classified as stage IV, in the same category as patients with distant metastatic disease, consistent with generally poor outcome in these patients. Moreover, while targeted therapy has improved outcomes in patients with metastatic RCC, surgery remains the cornerstone for treatment of advanced RCC, and patients with suspected T4 RCC should not be routinely excluded from surgery [7]. We and others have shown in the past that in spite of a surgically challenging scenario, resection of the primary tumor in patients whose RCC shows adjacent organ invasion is feasible without significantly increased morbidity, and could provide improved survival in patients with no distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…This subset of patients demonstrate poor outcomes with a 5-year survival rate of 20-30% and an estimated 10-year cancer specific survival rate (CSS) of 12% [5, 6]. Upfront aggressive surgery remains the standard of care for localized and locally advanced RCC and a cornerstone for the multimodal treatment of metastatic RCC [7, 8]. Nevertheless, tumors with adjacent organ involvement pose a challenging scenario even for experienced surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…Although 10 patients developed recurrence at a median time of 2.3 months, 5 (42%) patients were still alive at the time of analysis [7]. In another study of 26 patients at the Memorial Sloan Kettering Cancer Center (MSKCC), pancreas (23%) and bowel (23%) resections were among the more commonly resected organs, along with liver (39%), IVC (35%), vertebral body (31%), spleen (12%), and psoas muscle (7%); with 4 (15%) of those patients still alive at follow up [8].…”
Section: Discussionmentioning
confidence: 99%
“…Resection for locally advanced RCC has increasingly been performed with acceptable morbidity and mortality rates in the last few years [5,6], and there are some series describing such an aggressive approach with modest survival benefit in this group of patients [7,8]. Furthermore, clinical and pathological stage discrepancy is common in surgically treated patients which can have significant impact on clinical outcome [9].…”
Section: Introductionmentioning
confidence: 99%